Transformational Leadership of Kiai in Character Building of Islamic Boarding School Alumni: A Phenomenological Study - Sulaiman, Sulaiman; Kurniady, Dedy Achmad; Sa’ud, Udin Syaefudin; Aedi, Nur; Prihatin, Eka (Universitas Negeri Malang, 2026)
This study explores the influence of kiai (Islamic boarding school leader) leadership on character building of alumni from non-Salafi Islamic boarding schools using a phenomenological approach. Through in-depth interviews and thematic analysis with six phases of Braun and Clarke, the research involving one alumni participant identified four fundamental mechanisms: transformative learning based on exemplary leadership integrating knowledge transfer and character formation through role modeling, long-term internalization of religious values resistant to contemporary social change, capacity for value adaptation in plural society without compromising basic principles through critical inclusivism, and character sustainability through non-verbal modeling and informal dakwah strategies. Kiai leadership manifests transformational leadership principles uniquely by minimizing verbal rhetoric while maximizing concrete behavioral demonstration, emphasizing moral consistency over personal charisma, and prioritizing internal transformation over external compliance. The formed character is holistic, integrating cognitive dimensions of deep textual understanding, affective dimensions of value internalization, and psychomotor dimensions manifested in consistent social behavior. This research enriches transformational leadership literature by demonstrating that leadership effectiveness is contextual rather than universal, and contributes to character formation theory by identifying specific role modeling mechanisms in intensive learning environments, producing deep and sustainable character transformation.